Quantitative Evaluation of Water Vapor Permeability Coefficients of Earth Materials Under the Influence of Density and Particle Size Distribution - Jun Mu; Shenwei Yu (Buildings)
Earth materials are commonly utilized due to their excellent wet properties and environmental friendliness. However, previous research has primarily focused on the impact of additives on the water vapor permeability of earth materials, neglecting the influence of particle size distribution. This has also hindered the quantitative assessment of the water vapor permeability of earth materials. To advance the use of earth materials in building energy conservation, this study develops a mathematical model for the water vapor permeability coefficient of earth materials. This model is derived from experiments that measure the water vapor permeability coefficient of earth materials with varying densities and earth-to-sand ratios, employing both experimental measurements and theoretical analyses. After being adjusted by a quadratic function of error rate and density, the average error rate of the mathematical model decreased from 5.73% to 1.3%, indicating its accuracy. Furthermore, by utilizing this model, the impacts of density, clay, sand, and gravel on the water vapor permeability coefficient of earth materials were quantitatively examined. The results indicate a negative correlation between the water vapor permeability coefficient of earth materials and density. When the clay–sand–gravel ratio was 3.8:5.0:1.2, the vapor permeability of the earth materials was the worst, whereas when the gradation ratio was 4.6:3.4:2.0, the vapor permeability was relatively optimal. The findings of this research can provide a reference for the scientific quantification of the thermo-physical property indices of earth materials in green building design systems.